The Insectile Informe: H. P. Lovecraft and the Deliquescence of Form. Issue 3 (December 2019) - Collignon, Fabienne
Abstract : This article investigates the phonic materiality of sound, specifically of buzzing voices, in H. P. Lovecraft's 1930 short story "The Whisperer in the Darkness." The insectile is configured as a trope for the "outside" and as a formless entity, the latter rendered as an enfleshed voice. I am concerned with the interplay between form and formlessness, particularly as it pertains to sound, and the production of form, that is, how form and, conversely, formlessness are determined as political categories, not ontological givens. I use this approach, a focus on the valorization of form, to argue against recent scholarship, notably Graham Harman's Weird Realism (2012), claiming Lovecraft as a writer offering a deconstruction of "man" through perspectives other than human, when the latter remains absolutely understood according to what Sylvia Wynter calls the "coloniality of Being."